NILAI GIZI, DAYA CERNA PROTEIN DAN DAYA TERIMA PATILO SEBAGAI MAKANAN JAJANAN YANG DIPERKAYA DENGAN HIDROLISAT PROTEIN IKAN MUJAIR (Oreochromis mossambicus) - Haslina, Haslina; Muis, Siti Fatimah; Suyatno, Suyatno (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2006)
ABSTRACT Introduction: Patilo is one of traditional various snacks from Gunung Kidul that is made of fermented cassava waste and cassava starch. Fermentation is intended to reduce or eliminate the HCN content of cassava and to establish special flavour. The protein content of patilo is very low, therefore it can be enriched with animal protein from fresh water fish in form of fish flour or fish protein hydrolysate (FPH). Enrichment with fish protein hydrolysate has an advantage since it will be easier to digest by human because FPH better functional properties and higher solubility.Method: The study consisted of four activities that were 1) making/producing mujair FPH, 2) producing and enriched patilo with mujair FPH, 3) analyzed the nutritive values and protein digestibility of enriched and unenriched patilo and 4) analyzed the consumers acceptability of the products. The experiments were carried out in the 1) Food Engineering and Chemistry Laboratorium of Faculty of Agriculture Technology Semarang University, 2) Pilot Plan PAU and GMSK Laboratory of Bogor Institute of Agriculture, 3) Sidoardjo Village, Tepus Gunung Kidul. Variables being studied were nutritive value and protein digestibility of unenriched and enriched patilo with mujair FPH in several consumer acceptability in terms of flavour, taste, colour and texture. The study design was a complete random design of one factor in which the FPH was added in 5%, 10% and 15% concentration, each treatment repeated 3 times. Statistical analyses used for nutritive value and protein digestibility were Anova followed by Least Significant Difference test with 0,05 level of significancy Friedman and Wilcoxon Sign Rank test were used to test the organoleptic values both in the laboratory and in the field. Result:1) The nutritive value changes of raw enriched patilo were : a) significant decrease in water and carbohydrate content, b) significant increase in ash, fat and protein content compared to the unenriched patilo, 2) The nutritive value change of fried enriched patilo were : a) significant decrease in water and carbohydrate content, b) significant increase in fat, protein and energy content compared to the unenriched patilo, 3) The protein digestibility in raw and fried enriched patilo was significant higher than that without enrichement, 4) Patilo enriched with 10% mujair FPH was mostly liked by consumer either in the laboratory or in the field in term of taste, flavour and texture as for colour, all consumers prefered the unenriched patilo, 5) The changes of the nutritive values and protein digestibility were statistically significant in the enriched patilo, however from the nutrition point of view, only the increased of protein content (six folds increase) was meaningful. Conclusion: Patilo enriched with 10% mujair FPH is the most/well accepted by laboratory panelists and field consumers, and there was six folds increase in the protein content. Â  Key Word: Patilo, enrichment and fish protein hydrolysate. Â  ABSTRAK Â  Latar Belakang: Patilo adalah salah satu makanan jajanan tradisional Gunung Kidul yang diolah dari ampas singkong yang difermentasi dan dicampur dengan pati singkong. Kandungan protein dalam patilo sangat rendah, untuk itu perlu diperkaya antara lain dengan sumber protein hewani dari ikan air tawar baik dalam bentuk tepung ikan atau hidrolisat protein ikan (HPI). Tujuan: Penelitian ini bertujuan untuk 1). menganalisis nilai gizi patilo 2). menganalisis daya cerna protein patilo 3). menganalisis daya terima patilo goreng tanpa dan dengan penambahan HPI mujair Metode: Penelitian ini terdiri dari empat kegiatan yaitu: 1). pembuatan HPI mujair, 2). pembuatan dan pengkayaan patilo dengan HPI mujair, 3). pengujian nilai gizi dan daya cerna protein patilo tanpa dan dengan penambahan HPI mujair dan 4). uji penerimaan patilo baik di laboratorium maupun di lapangan. Variabel yang diamati adalah kandungan gizi patilo dan daya cerna protein patilo. Rancangan percobaan yang digunakan adalah Rancangan Acak Lengkap dengan 1 faktor yaitu HPI0=tanpa penambahan HPI, HPI1= penambahan HPI 5% dari berat ampas (b/b), HPI2=penambahan HPI 10 % dari berat ampas (b/b) dan HPI3=penambahan HPI 15% dari berat ampas (b/b), masing-masing perlakuan diulang sebanyak tiga kali. Analisis kandungan gizi dan daya cerna patilo dengan Anova, uji dilanjutkan dengan uji Least Significant Difference (LSD) pada taraf dan 5%. Untuk analisis uji organoleptik baik di laboratorium maupun di lapangan dengan uji Friedman. Perbedaan hasil akan dilanjutkan dengan uji lanjut Wilcoxon Sign Rank Test. Hasil: 1) Nilai gizi patilo mentah dengan penambahan HPI mujair dibandingkan tanpa penambahan HPI mujair adalah : a) terjadi penurunan kadar air dan kadar karbohidrat secara signifikan (Ï<0,05) dan b) terjadi peningkatan kadar abu, kadar lemak dan kadar protein secara signifikan (Ï<0,05), 2) Nilai gizi patilo goreng dengan penambahan HPI mujair dibandingkan tanpa penambahan HPI mujair adalah : a). terjadi penurunan kadar air dan kadar karbohidrat secara signifikan (Ï<0,05) dan b).terjadi peningkatan kadar lemak, kadar protein dan energi secara signifikan (Ï<0,05) 3). Daya cerna protein patilo mentah dan goreng dengan penambahan HPI mujair meningkat secara signifikan (Ï=0,000) dibandingkan tanpa penambahan HPI mujair pada semua konsentrasi, 4). Patilo dengan penambahan HPI mujair 10% paling disukai oleh panelis agak terlatih dan panelis konsumen anak sekolah berdasarkan skor rasa, bau dan tekstur. Untuk warna, panelis agak terlatih dan panelis konsumen anak sekolah memilih patilo tanpa penambahan HPI mujair dan 5). Secara statistik perubahan nilai gizi dan daya cerna protein bermakna kecuali untuk kadar abu patilo goreng, namun dari sudut gizi perubahan yang berarti hanya pada kadar protein yang mencapai 6 kali lipat. Simpulan: Patilo yang diperkaya dengan HPI mujair 10% paling disukai oleh panelis agak terlatih maupun panelis konsumen anak sekolah dan terjadi kenaikan secara signifikan pada kadar protein yang mencapai 6 kali lipat. Kata Kunci : Patilo, pengkayaan dan hidrolisat protein ikan Â  Â Permalink : http://ejournal.undip.ac.id/index.php/jgi/article/view/3243 Â